Direction of Trade Statistics September 2003. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2003)
The Direction of Trade Statistics Online service provides data on the value of merchandise exports and imports between each country and all its trading partners. The database includes: total bilateral and multilateral exports and imports aggregated at national or regional group level; data from 1948 at monthly, quarterly, and annual frequencies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet